5-Aminoimidazol-4-carboxamidrazones as potential antifungals: New advances to the action mechanism - Carvalho, Filipe (2019)
Chemical assays demonstrated that 5-aminoimidazole-4-carboxamidrazones are very susceptible to oxidation, and it was possible to identify reactive oxygen species during the oxidation process. The presence of acids inhibited oxidation of the compounds, since protonated form is much more stable and resistant to oxidation. Addition of antioxidants was also evaluated and, although some of the antioxidants tested were not effective, oxidation could be slowed down by de use of Vitamin C. Biological assays were also performed with Vitamin C and in acid medium. and antimicrobial activity decreased significantly, supporting the oxidation hypothesis.